Hybrid Nanoreactors: Coupling Enzymes and Small‐Molecule Catalysts within Virus‐Like Particles. Issue 1 (10th September 2014) - Patterson, Dustin; Edwards, Ethan; Douglas, Trevor
Abstract Virus‐like particles (VLPs) provide unique scaffolds for the construction of coupled catalytic systems by attachment and encapsulation of catalysts within their hollow interiors. The interior of VLPs provides an environment where catalysts of biological or synthetic origins can be confined, protected, and colocalized in close proximity with catalysts of different types. Herein, we utilize the P22VLP as a scaffold to construct a synthetic hybrid catalyst by attachment of a small organometallic catalyst to the interior colocalized with an encapsulated enzyme. This produces a complex and active coupled biomimetic catalyst system. By combining both enzymatic and synthetic catalysts together, new biologicalsynthetic hybrid materials can be produced that incorporate the best of both catalytic systems.